ASSOCIATION BETWEEN ENDOTHELIAL PROGENITOR CELLS AND VON WILLEBRAND FACTOR IN ASTROCYTIC GLIOMA - Das, Priscilla; Cheng, Tan Suat; Suppian, Rapeah; Ghani, Abdul Rahman Izaini; Bee, Yvonne Get (LIFE: International Journal of Health and Life-Sciences, 2015)
Astrocytic gliomas are highly aggressive and lethal brain tumours that depend on angiogenesis for growth. The endothelial progenitor cell (EPCs) and von Willebrand factor (vWF) involved in the formation of new blood vessels in astrocytic glioma. Objectives: This study aimed to investigate the association between circulating and tissue resident EPCs with vWF in astrocytic glioma patients. Methods: Blood specimen and brain tissue biopsy were collected from a total of 22 astrocytic glioma patients admitted to Hospital Universiti Sains Malaysia. Circulating EPCs (blood) and tissue resident EPCs (tissue biopsy) were characterized using EPC-specific markers, CD133 and VEGFR2 and quantified using fluorescenceactivated cell sorting analysis and immunofluorescence microscopy, respectively. The plasma vWF was measured by using commercialized Elisa kit (Cusabio Biotech Co.,Ltd). Results: The mean percentage of circulating EPCs was (0.01 ± 0.01%), brain tumor tissue EPCs (0.48 ± 0.38%) and adjacent normal brain tissue EPCs (0.18 ± 0.23%). The mean plasma vWF was 9.23 ± 7.57%. Positive correlation was found between brain tumor EPCs and plasma vWF (Spearman’s rho r = 0.45, p = 0.035). However no correlation was found between adjacent normal brain EPCs and plasma vWF. About 14 patients had (mild vWF level of> 5%), 8 patients had (moderate vWF level of 1-5%) and no patients had (severe vWF level of < 1%). The mean percentage of patients with mild vWF level was 12.48 ± 7.77% and moderate vWF level was 3.53 ±1.32%. There was a significant correlation between circulating EPCs and patients with mild vWF level(Spearman’s rho r = 0.63, p = 0.015). Conclusion: This study demonstrated that EPCs have significant positive association with vWF suggesting the homing of plasma vWF at the tumor site.